Near infrared reflectance spectroscopy for the determination of free gossypol in cottonseed meal - Lordelo, M.M. (2009)
Gossypol is a toxic polyphenolic compound produced by the pigment glands of the cotton plant. The free gossypol content of cottonseed meal (CSM) is commonly determined by the American Oil Chemists’ Society (AOCS) wet chemistry method. The AOCS method, however, laboratory-intensive, time-consuming, and therefore, not practical for quick field analyses. To determine if the free gossypol content of CSM could be predicted by near infrared reflectance spectroscopy (NIRS), CSM samples were collected from all over the world. All CSM samples were ground and a portion of each analyzed for free gossypol by the AOCS procedure (reference data) and by NIRS (reflectance data). Both reflectance and reference data were combined in calibration. The coefficient of determination (r2) and standard error of prediction (SEP) were used to assess the calibration accuracy. The r2 was 0.728, and the SEP was 0.034 for the initial calibration that included samples from all over the world. However, the r2 and SEP improved to 0.921 and 0.014, respectively, if the calibration was made using CSM samples only from the United States. These results indicate that a general prediction equation can be developed to predict the free gossypol content of CSM by NIRS. From a practical standpoint, NIRS technology provides a method for quickly assessing whether a particular batch of CSM has a free gossypol content low enough to be suitable for use in poultry diets.